The NPY Family of Peptides in Immune Disorders, Inflammation, Angiogenesis, and Cancer - Zukowska, Zofia; Feuerstein, Giora Z.; SpringerLink (Online service) (Basel : Birkhäuser Basel : Imprint: Birkhäuser, 2005)
Recent research indicates that the immune system and inflammatory reactions are governed and regulated by powerful neuronal mediators derived from the central and peripheral nervous system. The NPY family of peptides is a diverse group of neuropeptides that acts via multiple receptors, Y1-Y5, which are widespread not only in neurons but also in a variety of non-neural and immune cells. These peptides have been known as important regulators of many essential systems, such as blood pressure and cardiac function, food consumption and energy homeostasis. However, in recent years, they have also become recognized for their role as potent modulators of cell growth and immune functions with broad implications in chronic inflammatory diseases, cancer and angiogenesis. In this book, experts in the field analyze recent evidence supporting the role of NPY family of peptides in regulation of the immune/inflammatory system with special reference to its medical and therapeutic implications.
Biology of the NPY family of peptides, their receptors and processing enzymes -- Evolutionary perspective on the NPY-PYY-PP peptides and their receptors -- Function, distribution and molecular pharmacology of NPY-family receptors -- NPY processing in neuronal and non-neuronal tissues by proconvertases -- Dipeptidyl-peptidase IV and aminopeptidase P: molecular switches of NPY/PYY receptor affinities -- The NPY family of peptides in immune disorders and inflammation -- NPY, NPY receptors and DPPIV in innate immunity and autoimmune disorders -- NPY and phagocytic cell functions -- NPY in allergic and respiratory disorders -- NPY analgesia: moving from acute to chronic pain -- The NPY family of peptides and angiogenesis -- NPY as a mediator of neurogenic angiogenesis and revascularization of ischemic tissues -- NPY-induced angiogenesis in retinopathy and wound healing -- NPY in vascular inflammation, remodeling and atherosclerosis -- The NPY family of peptides as growth factors in neurodegenerative diseases and tumor biology -- NPY as a pleiotropic growth factor -- NPY and Hippocampal Neurogenesis -- NPY family of peptides in neural crest-derived tumors -- NPY family of peptides in endocrine, breast and prostate tumors -- Summary -- Future directions and therapeutic perspectives for NPY/PYYbased anti-inflammatory and tumor suppressor drugs.
Keywords: Immunology; Cell biology; Neurobiology; Cancer research; Immunology; Cell Biology; Neurobiology; Cancer Research